Hyperprogressive Disease in Cancers Treated With Immune Checkpoint Inhibitors - Shen, Pan; Han, Liang; Ba, Xin; Qin, Kai; Tu, Shenghao (Frontiers in Pharmacology, 2021)
ABSTRACT Immunotherapy, which takes advantage of the immune system to eliminate cancer cells, has been widely studied and applied in oncology. Immune checkpoint inhibitors (ICIs) prevent the immune system from being turned off before cancer cells are eliminated. They have proven to be among the most promising and effective immunotherapies, with significant survival benefits and durable responses in diverse tumor types. However, an increasing number of retrospective studies have found that some patients treated with ICIs experience unusual responses, including accelerated proliferation of tumor cells and rapid progression of the disease, with poor outcomes. Such unexpected adverse events are termed hyperprogressive disease (HPD), and their occurrence suggests that ICIs are detrimental to a subset of cancer patients. HPD is common, with an incidence ranging between 4% and 29% in several cancer types. However, the mechanisms of HPD remain poorly understood, and no clinical predictive factors of HPD have been identified. In this review, we summarize current findings, including retrospective studies and case reports, and focus on several key issues including the defining characteristics, predictive biomarkers, potential mechanisms of HPD, and strategies for avoiding HPD after ICI treatment.